Building Successful Startups : A Guide to Startup Development in the Czech Republic - Vraný, Marcel; Andera, Michal, 1984-; Pavlečka, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This diploma thesis investigates the Czech startup ecosystem's development, structure, and challenges, providing a comprehensive theoretical and practical analysis grounded in theoretical frameworks and stakeholder interviews. The theoretical part explores startup methodologies such as the Lean Startup, Design Thinking, and the Business Model Canvas, alongside a breakdown of key development phases, from ideation to exit. It further contextualizes the Czech environment through international comparisons with the United States and Spain, focusing on investment flows, regulatory constraints, ESOP adoption, and digital readiness. The practical part is based on qualitative research conducted through semi-structured interviews with startup founders and ecosystem stakeholders, identifying key bottlenecks, policy gaps, and cultural mindsets affecting growth. Findings are translated into actionable recommendations for entrepreneurs, investors, and policymakers to support the creation of globally competitive startups in the Czech Republic.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses